Ideas for the animated short : finding and building stories - Sullivan, Karen, 1958- (Focal Press, 2013)
This book is a conceptual toolkit for animators who wish to design 2-5 minute short films. Topics covered include creating a story, improving content, acting, characters, locations, dialogue, storyboarding, and staging.